2021
DOI: 10.3390/su13179728
|View full text |Cite
|
Sign up to set email alerts
|

The Construction Industry as the Subject of Implementing Corporate Social Responsibility (the Case of Poland)

Abstract: Companies of the construction sector face a significant impact on the environment and people: consume massive amounts of natural resources, emit pollutants, and generate large amounts of waste, are a place of danger and accidents at work. It is well established that implementation of CSR principles can lead to several economic, social, and environmental benefits. This is shown by numerous studies carried out in various countries among companies from different sectors of the economy. The aim of the article is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Large-sized industries receive the spotlight from various parties, which causes companies to spend more on CSR disclosures. Bernaciak et al (2021) revealed that the level of CSR implementation in large-scale industries provides positive image benefit to stakeholders, while small and medium enterprises consider CSR involvement as a sunk cost that does not bring more advantages. Large firms will disclose more information instead of small-scale business due to the politics that are confronted by largescale firms.…”
Section: H2 Profitability (Y1) Moderates the Effect Of Csr Disclosure...mentioning
confidence: 99%
See 1 more Smart Citation
“…Large-sized industries receive the spotlight from various parties, which causes companies to spend more on CSR disclosures. Bernaciak et al (2021) revealed that the level of CSR implementation in large-scale industries provides positive image benefit to stakeholders, while small and medium enterprises consider CSR involvement as a sunk cost that does not bring more advantages. Large firms will disclose more information instead of small-scale business due to the politics that are confronted by largescale firms.…”
Section: H2 Profitability (Y1) Moderates the Effect Of Csr Disclosure...mentioning
confidence: 99%
“…Large companies will also CSR disclosure information more broadly so that the firms' image will be better and later affect the increase in company value. Bernaciak et al (2021) revealed that the level of CSR implementation in large companies provides positive image benefits to stakeholders, while small and medium enterprises consider CSR involvement as a sunk cost that do not create more advantages. The finding of this research has implications for stakeholder theory, i.e., that the larger the size of an industry, the more stakeholders are involved.…”
Section: Firm Size Moderates the Effect Of Csr Disclosure On Firms Valuementioning
confidence: 99%
“…Civil engineering companies and construction companies have a significant impact on the natural environment and citizens due to their massive consumption of natural resources, large production of waste and emitting pollutants [26] causing danger and accidents at the construction site [27,28]. That is why the topic of CSR is of particular relevance for civil engineering companies and building construction companies, who aim to compensate for their negative impact on the environment and try to meet the expectations of environmental and socially conscious clients [29][30][31]. Duman,Giritliand McDermott [32] found that construction companies are aware of the growing importance of CSR.…”
Section: Specificity Of Interorganizational Corporate Responsibility ...mentioning
confidence: 99%
“…Nevertheless, the scale of company's activity and the country's specificity characteristics greatly influence CSR preferences. In [31], the motives, barriers, and effects of taking CSR principles by enterprises of the Polish construction sector were studied. Kowalczyk [33] found out that stakeholder pressure is the most important factor influencing CSR-culture and CSR-practice of construction companies in Europe.…”
Section: Specificity Of Interorganizational Corporate Responsibility ...mentioning
confidence: 99%
“…Even so, construction enterprises are often accused of acting irresponsibly [30][31][32]. This is because its business practices consume large amounts of natural resources, are a source of pollutants and wastes (dust, harmful gases, and noise [33,34]), impose a heavy burden on the environment [35], and interfere with the daily lives of residents while posing health risks to humans [36]. The industry lags far behind other industries in terms of awareness and implementation of CSR [37,38], with its decision makers placing a greater emphasis on financial costs than on environmental habitat issues [39].…”
Section: Introductionmentioning
confidence: 99%